People, Environment, and Future Sebuah Tinjauan atas Kesimpulan Pesimis Mengenai Lingkungan Hidup dan Masa Depan Manusia - Antonius Atosökhi Gea (Humaniora, 2012)
The study on the environment continuously attracted the attention of many people. The studies are generally based on a sense of concern over the condition of the natural environment and the future of mankind, that is an inseparable part of the natural environment as a whole. From the various existing studies, there is a rather pessimistic and also a more optimistic to look at the future of human beings in relation to the natural environment. One of the pessimistic conclusion is the result of a study conducted by Heilbroner, who  analyze a variety of facts and trends that continue to occur, ranging from the rapid increase in population of the world, environmental problems as well as the war, which was the unintended consequences could be avoided. From the results of his analysis Heilbroner finally came to the pessimists conclusion that no hope for the future of mankind. This conclusion has provoked a lot of debate, associated with the accuracy-related challenges he pointed out, as well as his pessimistic projection about the future of mankind. Based on the review conducted over this negative conclusion it is known that there are the possibility for human beings to be able to fix the situation, raise awareness, change attitudes, do something radically which gives positive impact to the safety of the environment. By making the study of Heilbroner  as a criticism and the triggers for the emergence of higher concern for the environment, we can hope that there is still hope for mankind to a better future.